2021
DOI: 10.3390/galaxies9010006
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Effects of Rotation in γ-ray Pulsars—Invited Review

Abstract: In this paper, we consider the relativistic effects of rotation in the magnetospheres of γ-ray pulsars. The paper reviews the progress achieved in this field during the last three decades. For this purpose, we examine the direct centrifugal acceleration of particles and the corresponding limiting factors: the constraints due to the curvature radiation and the inverse Compton scattering of electrons against soft photons. Based on the obtained results, the generation of parametrically excited Langmuir waves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…As it has been studied in detail by (Wright 2020) it is unrealistic to construct a monolithic spherical megastructure, because no material can be stable against internal gravitational stresses, implying that DSs should be composed of concentric rings. Then, one can show that the radius of the ring is given by (Osmanov and Berezhiani 2019;Osmanov 2021)…”
Section: Hot Megastructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been studied in detail by (Wright 2020) it is unrealistic to construct a monolithic spherical megastructure, because no material can be stable against internal gravitational stresses, implying that DSs should be composed of concentric rings. Then, one can show that the radius of the ring is given by (Osmanov and Berezhiani 2019;Osmanov 2021)…”
Section: Hot Megastructuresmentioning
confidence: 99%
“…Another interesting feature the observational signatures of megastructures will be characterised is the spectral variability. Osmanov and Berezhiani (2019) and Osmanov (2021) have examined ringlike megastructures around stars and pulsars and it was found that the hot rings oscillate nearby equilibrium positions leading (via the Doppler shift) to the spectral variability. The corresponding time-scales vary from several minutes (M-type stars) up to years (O-type stars).…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of centrifugal force depends on the configuration of magnetic field lines; the particles slide on. For example, if the force free approximation (curved field lines) is valid, efficiency will be relatively low [13], whereas for almost straight field lines, energies of centrifugally accelerated particles will be very high [14]. The transition to the force-free regime takes place in a very thin zone near the LC and most of the time particles accelerate on almost rectilinear co-rotating magnetic field lines [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the force free approximation (curved field lines) is valid, efficiency will be relatively low [13], whereas for almost straight field lines, energies of centrifugally accelerated particles will be very high [14]. The transition to the force-free regime takes place in a very thin zone near the LC and most of the time particles accelerate on almost rectilinear co-rotating magnetic field lines [14]. As has been shown in [15] the centrifugal force in the LC area is different for different species of particles (magnetospheric electrons and positrons).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation